PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TIPE SNOWBALL THROWING BERBANTUAN QUIZIZZ TERHADAP KETERAMPILAN BERPIKIR KRITIS DAN KETERAMPILAN SOSIAL SISWA KELAS V PADA PEMBELAJARAN IPS - Hartini, Sri Hastuti Anwa; Na’im, Mohamad; Alfarisi, Ridho (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to describe the critical thinking and social skills of fifth-grade students after implementing the Problem-Based Learning model of the Snowball Throwing type assisted by Quizizz. The research was conducted as classroom action research, with the subjects being fifth-grade students of SDN Sawaran Kulon 02, Kedungjajang District, Lumajang Regency, in the 2022/2023 academic year. Data were collected through observation and tests, and analyzed using an interactive analysis technique consisting of data reduction, data display, and conclusion drawing. The results showed that the Problem-Based Learning model of the Snowball Throwing type assisted by Quizizz had an impact on students’ critical thinking and social skills in social studies learning. Based on the data, after applying the Problem-Based Learning model assisted by Quizizz, there was an increase of 31.66%.